INCREASE "HIDAYAH" GINGER PRODUCTION THROUGH INSTAGRAM BRANDING AT DLANGGU MOJOKERTO HIGH SCHOOL - Ah Yusuf; Esti Yunitasari; Verantika Setya Putri; Dita Fajrianti (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2023)
Introduction: "Hidayah" ginger production during the Covid pandemic era has decreased. Instagram is currently a social media that influences product sales. The purpose of this community service is to increase the production of “Hidayah” ginger through Instagram branding with feed and reel updates about Hidayah ginger production and products. Methods: This community service uses pre and post-tests with a one-group design. The variable that is measured is knowledge which is measured through pre and post-tests. This community service training activity is aimed at students of SMA AL Hidayah Dlanggu Mojokerto. The population in this study amounted to 20 people. data analysis using SPSS 20 to see the frequency distribution. Results: The results achieved in this community service are that Dlanggu High School students can do product branding through Instagram, by creating product feeds and reels and production activities that can promote products so that product sales increase. In building ginger product branding, the ability that must be acquired and developed by students using Instagram is being able to create accounts, and interesting content about the production process and ginger products to increase product sales. Conclusion: Branding ginger Hidayah products through Instagram social media can increase sales of ginger Hidayah products and introduce ginger Hidayah to the wider community by creating an Instagram account as a media branding.